Children's librarian conducting storytime in the downtown library. - Unknown (Forsyth County Public Library, 1990)
Photo made in the 1990s.
Children's librarian Carol Laing conducting storytime in the downtown library.
Keywords: Forsyth County (N.C.) -- History -- Pictorial works; Forsyth County (N.C.) -- History -- Sources; Digital Forsyth; Forsyth County Public Library; Winston-Salem (N.C.)